Challenges of Deploying Broadband in Rural Uganda and Smart Technical Solutions to Address these Challenges - Mile, Anthony; Serumaga, Susan; Kizito, Patrick (School of Computing and Informatics, Makerere University, 2018)
Since the liberalization of the telecommunication sector in Uganda in 1998, the key services have been voice, data and low rate Internet. The backbone link to the rest of the world has been via satellite which is characterized by low bandwidth limiting broadband usage in Uganda. With the arrival of undersea cables at the East African coast, Uganda is now linked to the rest of the world via optic fiber which offers high bandwidth rendering access to broadband services. Internally, wired, Optic fiber and wireless technologies such as 3G mobile and WiMAX infrastructure have brought broadband services within reach of the urban population. These improvements have revolutionized telecommunication by making broadband access more affordable and enabling converged voice, data and video/entertainment services to the urban population. Rural areas with low level or absent grid power and telecommunication infrastructure to deliver such services are still in a broadband blackout. In this paper, we discuss the challenges to rural broadband deployment in Uganda and propose possible technical solutions to address these challenges.
Keywords: Broadband; WiMax; Wi-Fi